2015
DOI: 10.1158/2326-6066.cir-14-0001
|View full text |Cite
|
Sign up to set email alerts
|

Peptide/MHC Tetramer–Based Sorting of CD8+ T Cells to a Leukemia Antigen Yields Clonotypes Drawn Nonspecifically from an Underlying Restricted Repertoire

Abstract: Testing of T cell-based cancer therapeutics often involves measuring cancer antigen-specific T-cell populations with the assumption that they arise from in vivo clonal expansion. This analysis, using peptide/MHC tetramers, is often ambiguous. From a leukemia cell line, we identified a CDK4-derived peptide epitope, UNC-CDK4-1 (ALTPVVVTL) that bound HLA-A*02:01 with high affinity and could induce CD8+ T-cell responses in vitro. We identified UNC-CDK4-1/HLA-A*02:01 tetramer+ populations in 3 of 6 patients with ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…The model predicts the emergence of a limited number of dominant T cell clones, symbolizing antigen driven proliferation and a large number of low frequency clones representing a reservoir of T cell clones which are likely sustained through homeostatic mechanisms. [37,38,39] Recent observation of similar T cell receptor VDJ expressing clones dominating in different patients with a similar HLA type also lends credence to this model and its underlying premise. [40] Incorporating competition, with high affinity antigen directed T cell clones dominating lower affinity antigen directed clones (Supplementary Figure 3B SCT.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The model predicts the emergence of a limited number of dominant T cell clones, symbolizing antigen driven proliferation and a large number of low frequency clones representing a reservoir of T cell clones which are likely sustained through homeostatic mechanisms. [37,38,39] Recent observation of similar T cell receptor VDJ expressing clones dominating in different patients with a similar HLA type also lends credence to this model and its underlying premise. [40] Incorporating competition, with high affinity antigen directed T cell clones dominating lower affinity antigen directed clones (Supplementary Figure 3B SCT.…”
Section: Discussionmentioning
confidence: 71%
“…This hypothesis is supported by the earlier observation that patients who have oligoclonal T cell recovery following SCT may be more likely to be susceptible to alloreactivity. [37,44] Further support for the notion of oligoclonal T cell growth in response to high affinity and abundant minor histocompatibility antigens comes from the observation of clonal growth in mixed lymphocyte reactions (MLR) predicting loss of renal allografts [45]. MLR has also been used to study, alloreactive T cell clonal populations following SCT and has demonstrated the presence of a large number of dominant and low frequency clones over time.…”
Section: Discussionmentioning
confidence: 99%
“…Further validation of the model simulating normal physiology comes from the resulting steady state T cell repertoire approximating a Power Law distribution of the T cell clonal frequency for the entire repertoire [18, 19, 20]. The model predicts the emergence of a limited number of dominant T cell clones, symbolizing antigen driven proliferation and a large number of low frequency clones representing a reservoir of T cell clones, which are likely maintained through homeostatic mechanisms [29, 30, 31]. Recent observations of similar T cell receptor VDJ expressing clones dominating in different patients with a similar HLA type also lends credence to this model and its underlying premise [32].…”
Section: Discussionmentioning
confidence: 99%
“…The TCRβ-chain rearrangement of this clone was analyzed using a modification of another multiplexed RT-PCR protocol for single cell TCRβ analysis. 42 …”
Section: Methodsmentioning
confidence: 99%